PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN SOFTWARE ADOBE FLASH PROFESIONAL CS8 PADA MATERI SEGI EMPAT - Ashar Jurang Penatas Ashari; Iesyah Rodliyah (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2022)
Learning media is important in the learning process, however the use of learning media that is not appropriate to the needs of students will complicate the learning process. At SMPN 1 Mojowarno students are only asked to read textbook then they are given assigments via the whatsapp application. In addition, the rectangular material at the school only explained the formulas without ane explanation of how the formulas could be found, thus make the learning process less meaningfull The aims of this developmen is to produce learning media in the form of Adobe Flash Professioanal CS8 software that is valid, practical, and effective on rectangle material in online learning. The type of research used in this study was Research and Development by adopting the ADDIE development model. The stages carried out in this research are, Analysis, Design, Development, Implementation, and Evaluation. The result of material expert validation showed a percentage of 86,6% with very valid criteria, and the result of media expert validation showed a percentage of 88% with very valid citeria. The result of students response questionnaire showed a percentage of 84,7% in the practical category, and the individual learning outcomes test showed a average 80,9 and percentage of classical test 82,35% with effective category. So it can be concluded that the learningmedia that has been developed using Adobe Flash Professional software on rectangular material in online learning has met valid, practical and effective criteria. Keywords: Adobe Flash Professional CS8, Rectangel, Online learning